Lightweight Aggregate : A Growing Industry In New England ? Introduction - Henry N. McCarl (Society for Mining, Metallurgy & Exploration, 1964)
The New England States form the most northeastern portion of the continental United States and include Connecticut, Rhode island, Massachusetts, Vermont, New Hampshire, and Maine. These states have an aggregate population of over 10.5 million people, and an average annual population rate increase of about 1.3%. A great deal of new construction is required each year to meet the increasing demand for new homes, roads, offices, factories, and warehouses. Yet, prices of construction materials such as blocks and concrete are generally higher in New England than in other well populated areas of the United States. This is an indication of local demand being somewhat greater than supply, an atmosphere conducive to new developments in the production of construction materials. One such field of development is the rapidly growing Lightweight Aggregate Industry. Recent construction in Boston has used a great deal of lightweight aggregate. New structures using lightweight aggregate in lightweight concrete include the following: M.I.T.'s 20-story Earth Science Center and 17-story Married Students Housing Project Prudential Life Insurance Center, West End Redevelopment Project at Charles River Park, Hotel Americana, and the British-owned 33-story office building at 50 Pearl Street.